Lojalność pracownika: trwała wartość czy anachroniczna cnota? - Lewicka-Strzałecka, Anna (Człowiek i Społeczeństwo, 2020)
The article tries to answer the question whether employee’s loyalty has any sense in the present day reality, when people change their job much more often than ever before and firms can appear and disappear very quickly. As the notion of loyalty is complex and polysemous, the first part of the article is devoted to the philosophical reflection on this issue. Next, the main arguments in the discussion on the employee’s loyalty are reconstructed and the pattern of loyal employees based on managerial experience is shown. This leads to the conclusion that there is no universal answer to the question about the sense of employee’s loyalty because it depends on the meaning of the term of loyalty and specific attributes of the organization for which the employee works. However, in some circumstances loyalty has the potential to contribute significantly to the employee’s fulfillment and to enhance the economic results of the organization. The main challenge for researchers is to identify these circumstances and conditions.